Knowledge Management Strategies for Enhancing Competitiveness: Case Studies of Applied Bachelor of Manufacturing Engineering Programs at a Manufacturing Polytechnic - Rizqa Ula Fahadha; Muhammad Syamsul Maárif; Budi Yulianto (BACA: Jurnal Dokumentasi dan Informasi, 2026)
Knowledge management has a crucial role in higher education institutions to achieve competitive advantages, spur innovation, and adapt to changes that occur in the industry. In the Applied Bachelor of Manufacturing Engineering Program at a polytechnic, the application of good knowledge management significantly improves the professionalism and ability of the graduates. However, the program faces demographic challenges: more than half of its teachers are aged 50 and over, and the results of the Internal Quality Audit (AMI) show that its competitiveness is still low. This issue raises concerns about the loss of core knowledge as well as the sustainability of undocumented knowledge transfer. This study aims to find these obscure areas as well as design a knowledge management strategy by combining AMI methods and Knowledge Management Capability Assessment (KMCA) to assess the state of the organization. Actor analysis was carried out using Interpretive Structural Modeling (ISM), and strategy priorities were prepared using the Analytical Hierarchy Process (AHP) Method, which involved 12 experts (from academia and practitioners). The results of the KMCA assessment indicate that the organization's current capabilities are 2.5 out of 5, confirming the high uncertainty arising from knowledge management systems that still depend on individuals. Based on the weighting of AHP, this study proposes four main strategies io mitigate these uncertainties: (1) the development of integrated digital platforms to support higher education management (51.3%), (2) increasing the integration of industrial knowledge (51.7%), (3) optimizing local knowledge (49.9%), and (4) implementing community-based knowledge management strategies (50.6%). As a follow-up, future research should focus on developing evaluation models to assess the effectiveness of digital platforms and on exploring the use of knowledge to align curriculum with industry needs.